4x+9=2x-6 2x=-15 x=-7.5 x equals -7.5.
2x must equal 12 so x is 6.
2x + 3 = 92x = 9 - 32x = 6x = 6/2x = 3
6 + 2x =2(3 + x)
-2x-6= -2x-6Another answer:-2x-6 = 2x+6-2x-2x = 6+6-4x = 12x = -3
4x+9=2x-6 2x=-15 x=-7.5 x equals -7.5.
2x must equal 12 so x is 6.
x=1
2x + 3 = 92x = 9 - 32x = 6x = 6/2x = 3
I believe the converse is: if 2x equals 6 then x equals 3 inverse: if x doesn't equal 3 then 2x doesn't equal 6 contrapositive: if 2x doesn't equal 6 then x doesn't equal 3
8x-7 plus 2x equals 6 plus 5x plus 2?
6 + 2x =2(3 + x)
2x + 6 - 6x = 30= 6 - 4x = 30= -4x = 24= 4x = -24= x = -6
-2x-6= -2x-6Another answer:-2x-6 = 2x+6-2x-2x = 6+6-4x = 12x = -3
2x-11
5 - 2x = 8 x = -1 and 1/2 4x = 6 x = 6/4 or 3/2
hujkImproved anwser:2x+6 = 7x-42x-7x = -4-6-5x = -10x = 2